"It's a war! It's a battle! It's a fight!": Do militaristic metaphors increase people's threat perceptions and support for COVID‐19 policies?. (2nd September 2021) - Schnepf, Julia; Christmann, Ursula
Abstract : At the beginning of the COVID‐19 pandemic, governments around the world employed militaristic metaphors to draw attention to the dangers of the virus. But, do militaristic metaphors truly affect individuals' perceived threat of the COVID‐19 virus and increase their support for corresponding restrictive policies? This study assessed the effects of fictitious newspaper articles that described COVID‐19 policies using similarly negatively valenced metaphors but with differing militaristic connotations (e.g., "war" vs. "struggle"). Overall, data from three framing experiments ( N  = 1114) in Germany and the United States indicate limited evidence on the effectiveness of the tested militaristic metaphors. In the U.S. context, the non‐militaristic concept of struggle was consistently more strongly associated with the desired outcomes than militaristic metaphors were. In Studies 2 and 3, we also tested whether reporting using a narrative or straightforward facts had additional influence on the framing effect. A congruency effect of the use of a narrative and of warfare metaphors was found in the German sample, but not in that of the United States. Results of post‐experimental norming studies ( N  = 437) in both countries revealed that the metaphor of war is associated with people ascribing greater responsibility to their governments, whereas the concept of struggle triggers a sense of individual responsibility. These results are discussed in terms of the usefulness and appropriateness of militaristic metaphors in the context of a pandemic.